2023
DOI: 10.1111/ene.16099
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risdiplam efficacy in 5q spinal muscular atrophy: A systematic comparison of electrophysiologic with clinical outcome measures

Tobias Kessler,
Georges Sam,
Wolfgang Wick
et al.

Abstract: BackgroundTo assess compound muscle action potential (CMAP) amplitudes as electrophysiologic markers in relation to clinical outcome in adult patients with 5q‐linked spinal muscular atrophy (SMA) before and during treatment with risdiplam.MethodsIn this monocentric longitudinal cohort study, CMAP of 18 adult patients with SMA type 2 or 3 were assessed at baseline (T0) and after 10 months (T10) of risdiplam treatment. CMAP amplitudes of the median, ulnar, peroneal, and tibial nerves were compared with establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Concerning risdiplam, no clinical trials in adult patients have been conducted, although published clinical trials of risdiplam have included some adult patients [ 22 ]. In a monocentric longitudinal cohort study, HFMSE and Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP INTEND) scores increased in parallel with increases of CMAP amplitudes in both median nerves in 18 adult patients with SMA type 2 or 3 treated with risdiplam during a 10-month treatment period [ 23 ]. Observational studies, meta-analysis and real life will likely define its therapeutic effect in adult patients [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning risdiplam, no clinical trials in adult patients have been conducted, although published clinical trials of risdiplam have included some adult patients [ 22 ]. In a monocentric longitudinal cohort study, HFMSE and Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP INTEND) scores increased in parallel with increases of CMAP amplitudes in both median nerves in 18 adult patients with SMA type 2 or 3 treated with risdiplam during a 10-month treatment period [ 23 ]. Observational studies, meta-analysis and real life will likely define its therapeutic effect in adult patients [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In SMA, the alpha motor neurons of the spinal cord are genetically affected, resulting in progressive muscle weakness and the development of muscle atrophy. It has been shown that 18 months of nusinersen treatment in children dramatically increases the number of motor neurons [25], and 10 months of risdiplam treatment in adult patients increases the active motor unit pool [26].…”
Section: Purpose and Hypothesis Of The Studymentioning
confidence: 99%
“…In SMA, the alpha motor neurons of the spinal cord are genetically affected, resulting in progressive muscle weakness and the development of muscle atrophy. It has been shown that 18 months of nusinersen treatment in children dramatically increases the number of motor neurons [ 26 ], and 10 months of risdiplam treatment in adult patients increases the active motor unit pool [ 27 ].…”
Section: Introductionmentioning
confidence: 99%